2021
DOI: 10.1186/s12866-021-02260-9
|View full text |Cite
|
Sign up to set email alerts
|

Benzylpenicillin-producing Trichophyton erinacei and methicillin resistant Staphylococcus aureus carrying the mecC gene on European hedgehogs – A pilot-study

Abstract: Background A high carriage rate of methicillin-resistant Staphylococcus aureus with the mecC gene (mecC-MRSA) has been described among Wild European hedgehogs (Europeaus erineaus). Due to this frequent occurrence, it has been suggested that hedgehogs could be a natural reservoir for mecC-MRSA. However, the reason why hedgehogs carry mecC-MRSA remains unknown, but it has been hypothesized that mecC-MRSA could have evolved on the skin of hedgehogs due to the co-occurrence with antibiotic producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The SCC mec are considered mobile genetic elements that could harbour AMR genes other than the mec [ 7 ]. The mecA gene (encoding PBP2a) has been detected in most MRSA isolates of animals, humans and the environment [ 8 ]. However, the origin and reservoir host of the mecC gene (which encodes the PBP2c) in MRSA has not been fully determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCC mec are considered mobile genetic elements that could harbour AMR genes other than the mec [ 7 ]. The mecA gene (encoding PBP2a) has been detected in most MRSA isolates of animals, humans and the environment [ 8 ]. However, the origin and reservoir host of the mecC gene (which encodes the PBP2c) in MRSA has not been fully determined.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, mecC was related with livestock associated (LA)-MRSA; however, it's continued and increased detection in wild animals indicates that mecC -MRSA is primarily associated with wildlife [ 9 ]. This suggests that mecC -MRSA could be considered as wildlife-associated MRSA (WA-MRSA) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis that the evolution of mecC -MRSA was driven by natural selection is supported by studies from northwestern Europe and New Zealand that showed that hedgehogs are frequently colonized with the dermatophyte T. erinacei , which produces a penicillinase-labile penicillin-like substance that was recently identified as penicillin G 12 19 . To test our hypothesis, we examined the distribution of mecC -MRSA and other S .…”
Section: Mainmentioning
confidence: 62%
“…erinacei is widespread among hedgehogs in New Zealand and northwestern Europe and that isolates from both continents produce a penicillinase-labile penicillin-like substance 12 19 , and a recent study characterized penicillin G from T . erinacei in Sweden (the presence of other β-lactams was not investigated) 19 . This suggests that penicillin-producing T .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of MRSA in wildlife without exposure to antibiotics has been recently reviewed (Heaton et al, 2020: Silva et al, 2020, showing that most MRSA isolated from wild animals are mecC positive. The dissemination of this mechanism of resistance (García-Álvarez et al et al, 2011;Shore et al, 2011) in freeliving animals and river waters (Porrero et al, 2014a) suggests that the natural environment may be a reservoir of mecC gene, and indeed, a cocolonisation of hedgehogs with S. aureus and dermatophytes that produce penicillin provides a selective pressure favouring mecC in the wild (Dube et al, 2021;Larsen et al, 2022;Smith & Marples, 1965).…”
mentioning
confidence: 99%